Microstructure evolution of AZ91 alloy processed by a combination method of equal channel angular pressing and rolling - Qiong Xu; Aibin Ma; Yuhua Li; Jiapeng Sun; Yuchun Yuan; Jinghua Jiang; Chaoying Ni (Journal of Magnesium and Alloys, 2020)
In the present work, AZ91 alloy was successfully processed by equal channel angular pressing (ECAP) for up to 16 passes and rolling (R) for multiple passes with a total reduction of 75% in addition to a combination method with ECAP plus rolling (ECAP+R). The effects of various processes (ECAP, R and ECAP+R) on microstructure evolution were analyzed and the influence of ECAP process on the rolling performance was examined. The result shows that ECAP contributed to a homogenous grain structure and formed a texture with higher Schmidt factors that was easy for rolling. A plate with smoother surface and reduced edge cracks was observed in the ECAP+R process than in the single R process. Although the microstructure of the alloy was similar after ECAP+R and R process, the sample of ECAP+R was more refined and had stronger second phase precipitation than the sample of R, which resulted in better rolling characteristics, along with the external surfaces. Keywords: AZ91 alloy, ECAP and rolling, “ECAP-modified” structure, Second phase precipitation, Texture